2019
DOI: 10.1021/acs.jced.9b00296
|View full text |Cite
|
Sign up to set email alerts
|

Relative Permittivity of Dipolar Model Fluids from Molecular Simulation and from the Co-Oriented Fluid Functional Equation for Electrostatic Interactions

Abstract: The relative permittivity of dipolar fluids is important in many industrial and scientific applications, e.g. whenever electrolytes or electromagnetic fields are present. For non-polarizable model molecules, it is directly linked to the mutual molecular orientation and thereby usually not accessible by equations of state. However, the recently developed Co-Oriented Fluid Functional Equation for Electrostatic interactions (COFFEE) allows for calculating the orientation

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…As in our previous work, , we study Stockmayer-type model fluids that consist of the Lennard-Jones (LJ) potential and a superimposed point dipole, resulting in the total potential energy U of a system of N particles given by Here, σ LJ and ϵ LJ are the LJ size and energy parameters, respectively, r ij is the distance between particles i and j , is the distance between the dipoles on particles i and j , ε 0 is the vacuum permittivity, μ is the magnitude of the dipole moment, and φ i ′, φ j ′, and γ ij ′ are the angles describing the mutual orientation of the dipoles. Figure shows a depiction of the angles in the dipole–dipole potentials used in the present work.…”
Section: Studied Fluids and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As in our previous work, , we study Stockmayer-type model fluids that consist of the Lennard-Jones (LJ) potential and a superimposed point dipole, resulting in the total potential energy U of a system of N particles given by Here, σ LJ and ϵ LJ are the LJ size and energy parameters, respectively, r ij is the distance between particles i and j , is the distance between the dipoles on particles i and j , ε 0 is the vacuum permittivity, μ is the magnitude of the dipole moment, and φ i ′, φ j ′, and γ ij ′ are the angles describing the mutual orientation of the dipoles. Figure shows a depiction of the angles in the dipole–dipole potentials used in the present work.…”
Section: Studied Fluids and Methodsmentioning
confidence: 99%
“…28 In a previous work, using a comparison to molecular simulation data we have shown that COFFEE is able to predict the relative permittivity of Stockmayer-type model fluids in the saturated liquid and vapor states, at least qualitatively. 29,30 In this work, we extend this study to the homogeneous liquid, vapor, and supercritical regions. We assess the predictions obtained with COFFEE 27 for the relative permittivity of Stockmayer-type model fluids by comparison with results from molecular dynamics (MD) simulations.…”
Section: ■ Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The ODF quantifies how neighboring molecules are mutually oriented. Such information on the fluid structure is useful for the parametrization of equations of state that give access to the relative permittivity [23,24].…”
Section: Orientational Distribution Functionmentioning
confidence: 99%
“…In addition to previous validations of the ms2 implementation [24,34,35] by comparison to literature data, the dielectric constant of two water models and two methanol models at ambient conditions was computed with ms2. Again, the reaction field method with conducting boundary conditions was used to treat longrange electrostatics.…”
Section: Dielectric Constantmentioning
confidence: 99%